Effects of Sipgeondaebo-tang Pharmacopuncture Extracts on the Collagenase Activity and Procollagen Synthesis in HS68 Human Fibroblasts and Tyrosinase Activity Original Articles - Lee Sena; Kim Myung-Gyou; Kim Myoung-Hee; Kim Hyung-Jun; Jo Hak Jun; Leem Kang-Hyun (Korean Pharmacopuncture Institute, 2011)
Objectives: This study was designed to investigate the collagen metabolism and tyrosinase activity of Sipgeondaebo-tang Pharmacopuncture extracts (SP). Methods: The effect of SP on type I procollagen production and collagenase activity in human normal fibroblasts HS68 after UVB (312 nm) irradiation was measured by ELISA method. The tyrosinase activity after treatment of SP was measured as well. Results: Type I procollagen production was recovered by SP in UVB damaged HS68 cells. The increased collagenase activity after UVB damage was significantly recovered by SP. The tyrosinase activity was significantly reduced as well. However, the L-DOPA oxidation was not changed. Conclusion: SP showed the anti-wrinkle effects and whitening effects in vitro. These results suggest that SP may be a potential pharmacopuncture as an anti-aging pharmacopuncture treatments.